الأداء البیئي كمدخل حدیث لاكتساب م ا زیا تنافسیة للمؤسسات الصناعیة -شركة نوكیا نموذجا- - amara, salma (Finance and Business Economies Review, 2018)
Industrial institutions seeking to achieve competitive advantages based on several strategic criteria, the environmental dimension has become the standard of achieving sustainable competitive under the globalization of markets and rival unit in the world today, this led to the institutions seek to Achieve environmental performance in various activities, the study discusses how the environmental performance to gain competitive advantages for industrial enterprises through integration of environmental considerations into its strategies and objectives in the long term, with reference to Nokia corporation as a model for environmental performance